Factores epidemiológicos y clínicos asociados al éxito del tratamiento de la tuberculosis multidrogorresistente en pacientes de Loreto 2018 – 2023 - Ruiz Davila, Lincol (2024)
General objective: Determine the association between the epidemiological and clinical factors of multidrug-resistant tuberculosis (MDRTB) and the success of treatment in patients from Loreto during the period 2018 – 2023. Material and methods: Quantitative study with a non-causal cross-sectional design. The sample will consist of all TBMDR cases in the Loreto region registered in the Tuberculosis Management Information System (SIGTB). Results: Epidemiological and clinical data will be presented in tables and graphs using the SPSS v25 statistical program and the association between the study variables will be determined using the chi-square test. Conclusions: Epidemiological and clinical factors of patients with TBMDR in the Loreto region may condition the success of treatment.